Understanding the effect of internal and external factors on households’ willingness to sort waste in Dammam City, Saudi Arabia - Labib, Ossama; Abd Manaf, Latifah; Sharaai, Amir Hamzah; Mohamad Zaid, Siti Sarah (MDPI, 2021)
The acceleration of growth in the population in Saudi Arabia and the increase in municipal solid waste generation have caused a problem in Dammam city: an increase in solid waste production. Therefore, solid waste sorting is an important practice of municipal solid waste management. The main objectives in this research are understanding the effect of internal and external factors on household willingness in sorting waste in Dammam city and studying the attempts to construct a theoretical research model by adding market incentives, government facilitators, and awareness into the popular planned behaviour theory to explain residents’ waste sorting intentions. The data collection and analysis are based on the questionnaire study, which is based on the questionnaire survey data from 450 households in Dammam. This study revealed that social influence significantly predicts households’ willingness to sort and recycle, that is, to promote recycling. Additionally, the variable social influence has a significant but low influence on households’ willingness to sort and recycle. The result of the structural equation model shows that perceived behavioural control significantly predicts households’ willingness to sort and recycle waste. This finding is consistent with the theoretical expectation. Therefore, this research shows that attitude, social influence, perceived behavioural control, market incentives, government facilitators and awareness positively and significantly affect residents’ waste sorting intentions. Additionally, this research corroborates the discrepancy between internal and external variables.